БАБУРДЫҢ «БАБУРНАМА» ДӨРЕТПЕСИ ҲӘМ ҚАРАҚАЛПАҚ ӘДЕБИЯТЫНДАҒЫ ЭПИКАЛЫҚ ЖАНРЛАР - Бекбергенова, М.Д. (SCIENCE and SOCIETY, 2018)
The article deals with the issues of comparative study of the famous work «Baburnama» of the great representative of Uzbek literature, classic of Uzbek literature of the XVI century, the poet and writer Zakhiriddin Mukhammad Babur, the genre features of this work of this work, plot and composition, issues of typological connection of memoir genre and literary epic genre. In particular, the author studies typological relationships with the novel «Karakalpaknama» of the famous writer of the XX century Karakalpak literature T.Kaypbergenov.